The mapping as a cooperative learning strategy to develop the writing skills amongst ninth grade students at unidad educativa Marieta de Veintimilla. Academic period 2014-2015 - Sánchez Azuero, Mirian Carmen (2016)
This investigation was focused on the use of the mapping as a cooperative learning strategy in order to improve the writing skills with a sample of ninth grade students at Unidad Educativa Marieta de Veintimilla. The methods used were: the scientific, descriptive, hypothetic-deductive and analytic-synthetic. They were used to describe the data, analyze the results and explain the problem and conclusions. The test was used to measure the writing knowledge on students and the questionnaires was used to know the students behaviors for working cooperatively in the classroom. The results evidenced the progress in the students’ achievements during the intervention plan, they increased the writing skills and they worked cooperatively in classes. It conclude that using of mapping as a cooperative learning strategy was effectively and it encouraged students to develop writing skills. In addition, a recommendation was to continue working with this strategy with students in that institution